A escala cartográfica na ponta dos dedos: contribuição das maquetes táteis na construção da noção de proporção no espaço vivido - Silva, Flávia Gabriela Domingos (2015)
The School Geography, as well as the school in general, has the responsibility to allow civic education of their students, which, from critical and autonomous positions can transform their social realities. It is considered that the Cartography takes great relevance in geographical studies, since it allows to analyze phenomena and objects through its spatiality. Among the several concepts of Cartography stands out the cartographic scale, understood as the similarity ratio between the area in the real and its representation, in other words, it is a relation of quantifiable proportion. However, the notion of proportionality is built, first, in non-quantifiable terms, from the relations of first and second order and the establishment of perceptual measures. Therefore, understanding the cartographic scale can be better carried from the work with the notion of non-quantifiable proportion present in the student living space. Assuming that the visual impairment limits the apprehension and comprehension from the space, it becomes important think about on the construction of the notion of proportion and the concept cartographic scale with VIs students, since such knowledge can enable other learning in relation to Geography and contribute to the development of skills orientation and mobility of these students. In this context, it was defined as objective of this research assess the contribution of tactile models to understand the notion of proportionality and cartographic scale by the students with visual impairment. Therefore, was adopted as methodology, the method of participatory research, establishing as search field the Centro Brasileiro de Reabilitação e Apoio ao Deficiente Visual (CEBRAV). In this institution were made steps monitoring/observation of subjects of the research; materials test; elaboration, manufacture and evaluation of tactile models; planning and development of didactic sequence; evaluation and analysis of the proposal. It is noteworthy that the tactile models, built from the theoretical-methodological foundations of the Tactile Cartography, allowed the construction of the notion of proportionality non-quantifiable and some aspects of the concept of cartographic scale, enabling moreover, show alternative solutions to the understanding of this concept, in quantifiable terms.